Identification of Red Meranti Group (Shorea spp., Dipterocarpaceae) Saplings Based on Variations in the Morphological Features of Quantitative Leaves - Nur Mufarhatun; Iwan Hilwan; Henti Hendalastuti Rachmat (Pusat Penelitian dan Pengembangan Hutan, 2021)
Shorea is the largest genus within the family of Dipterocarpaceae, a major timber tree dominating tropical forest in South East Asia. The genus of Shorea has many similarities, and species identification is often tricky. Most Shorea (Dipterocarpaceae) species perform as a big emergent tree; thus, species discrimination at seedlings level will benefit practical use in the field scale. A study of variations of leaf morphology and color on Red Meranti seedlings growing in an experimental nursery. A total of 450 individuals of 29 species of the Red Meranti were measured for their leaf characters. Data analysis was performed using the application R Statistics 3.6.0, RawTherapee 5.5, ImageJ 1.32, nixsensor, and encycolorpedia.id to obtain the leaf color of the observed species. Cluster analysis (Hierarchical Cluster Analysis) and Principal Component Analysis (PCA) were executed using IBM SPSS Statistics 25. The results showed that 11 of 13 observed leaf characters were, all variables support the grouping and species kinship, and those can be as determinants, except for AS and BS. Leaves color may be helpful in species determination only if transformed into digital color. This study result supports current taxonomical grouping based on flower and fruit characteristics.